THE SOUND OF EVIL: A PERSPECTIVE OF COMPARATIVE LITERATURE - Purnomosasi, Lusia Kristiasih Dwi (Universitas Negeri Surabaya, 2014)
The representation of evil in The Scarlet Letter, Madam Bovary, Anna Karenina, and Lady Chatterley?s Lover is a choice to be compared by the theory of comparative literature of Claudio Guillen.It is called thematology. It is based on the assumption that a theme will be different as it is accepted by different cultures. Internationality is applied among others. The evil functions as a representation of a sinner in The Scarlet Letter in line with external marital affairs by the main character. It is due to the belief of witch that leads to the special woman. The witch as the representation of evil changes to the beggar in Madam Bovary and a railway station officer in Anna Karenina. Both reflect the different social stratification as the effect of materialism. Lady Chatterley?s Lover has transformed to an invisible representation of evil. It is the mentality of capitalism. The transformation of those evil in the novels is created from the stereotype towards the cursed by society. It deals with the belief and status.